P21 Cardiac metabolism in patients with heart failure with mid-range ejection fraction. (21st March 2018) - Hundertmark, MJ; Rodgers, CT; Rider, O; Neubauer, S; Mahmod, M
Abstract : Rationale: Disturbance in cardiac energy metabolism is a key feature of heart failure (HF). It is unknown whether HF with mid-range left ventricular (LV) ejection fraction (HFmrEF), defined by LVEF 40%–49%, represents a separate clinical entity and whether there are distinct cardio-metabolic changes compared with HF patients with more severely reduced EF (HFrEF – LVEF <40%). We sought to investigate this by assessing myocardial energetics (phosphocreatine-to-adenosine triphosphate – PCr/ATP) and myocardial triglyceride (MTG) content in both HFmrEF and HFrEF. Methods: 53 subjects (13 HFmrEF, 13 HFrEF and 25 age, sex and BMI-matched controls) underwent cardiovascular magnetic (MR) resonance at 3 Tesla (3T) to assess left ventricular (LV) volumes and function, 31P-MR spectroscopy (MRS) to measure myocardial PCr/ATP, and 1H-MRS to measure MTG content. Results: There were no significant differences in PCr/ATP ratios between the two HF groups (HFmrEF 1.69±0.39 vs HFrEF 1.64±0.41 HFrEF, p<0.05), and both were significantly lower than controls (1.96±0.27, p<0.05). Similarly, MTG was not significantly different between HFmrEF (0.61%±0.39%) and HFrEF (0.71%±0.49%), both significantly higher than in controls (0.42%±0.16%, p<0.05). Interestingly, similar levels of PCr/ATP and MTG changes were observed in both HF groups despite significant differences in LV volumes (HFmrEF 192±45 vs HFrEF 270±92, p<0.001) and EF (HFmrEF 46±3 vs HFrEF 31±6, p<0.001). Conclusion: Our results indicate no differences in energetic and lipid derangement between HFmrEF and HFrEF. This emphasises the need for a new phenotyping model for HF patients based on factors other than LVEF.